PROPOSED MARKETING PLAN FOR INCREASING PASSENGER LOAD FACTOR OF NAM AIR BANDUNG-SURABAYA ROUTE - Ari Pramono Putri, Christina
In the past five years, domestic passengers have increased by 17%. The increasing number of domestic passengers has encouraged all airlines to expand market share by opening routes in the regional region. Bandung is one of the potential areas for domestic flights, so Nam Air is interested in opening its first flight service from Bandung in 2015 with the Bandung-Surabaya route. In February 2019, this route experienced a decrease in passenger load factors which only reached 36%, even though the domestic flight PFL average reached 78%. In an effort to improve the PFL, Nam Air focuses on consumer elements by understanding the attributes affecting their customers in making decisions to increase the percentage of passenger load factors on the Bandung-Surabaya route. The research methodology in this research is the marketing research theory with a research approach using the discrete choice model to understand and predict decision-maker choices from a discrete alternative from several choices. There are 3 alternative airlines operating on Bandung- Surabaya route. In making the stated preference (SP) questionnaire, the efficient design was used with NGENE application support which produced 8 questions in three different blocks. Furthermore, the questionnaire was distributed online to 235 respondents and collected observational data as much as 1880. The results of the questionnaire were then processed using the BIOGEME application to estimate the multinomial logit (MNL) model, so that researchers found significant attributes affecting passenger choice. By processing all attributes, the results show that only the IN price attribute (t-test = -5.53) and JT (-2.01) are significantly influential. Furthermore, the researchers processed all brand attributes with significant results, namely JT (-20.04) and QG (, 244). The results of the elasticity analysis, the price of the three alternative airlines is elastic in the consumer's decision with the value of IN (-1,6), JT (-7,4), (-1,3). The researcher propose a Marketing Model with a three Sub Model, the model are achieve break even volume, adjust prices with discounts and promos, build a strong brand for Nam Air. The overall Sub Model arranged in 19 marketing programs. Next the Researcher also conducts Cost and Benefit analysis to produce the right implementation and marketing budget.